The Influence of Leadership Communication on Employee Performance of PT. Duta Karya Bersatu Surabaya - Refera Fi Sabillah; Ety Dwi Susanti (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Communication is needed in various areas of human life, including in the economic sector, namely business. Communication is important in an organizational group. Employee performance can also be interpreted as the results achieved by an employee in carrying out his duties and responsibilities in working in the company. This research is to find out how the influence of leadership communication on the performance of employees of PT. Duta Karya Bersatu. The type of research in this study is quantitative research. The scale used by the researcher is the Likert scale. The sample in this study is all employees of PT. Duta Karya Bersatu totaling 34 people. Simultaneous leadership communication has an influence of 13.6%, with a significance value (0.032< 0.05) while 86.4% of employee performance is influenced by other variables that are not studied. It is important for companies to continue to develop strong communication to improve employee performance, in order to advance and strengthen the company's foundation.